Artists Unknown: The Poetics of Anonymity in Jean Richepin's Braves gens. (1st April 2013) - Forrest, Jennifer
<x xml:space="preserve">Abstract</x> In Jean Richepin's Braves gens, roman parisien (1886), the composer Yves de Kergouët and his spiritual counterpart, the mime Tombre, strive to put into practice the principles of a revolutionary theory of art they formulated with other members of a cénacle ten years earlier. Their dream of an 'art absolu' is threatened first by a capitalist economy that would have them compromise their ideals in the quest for comforts and laurels, and second by the art market, whose aesthetic opportunists are not above expropriating and exploiting the work of other artists. Yves and Tombre's refusal to compromise entails the abandonment of those bourgeois genres seen to corrupt the artist and the adoption of forms possessing none of the benefits associated with artistic success. Yves abjures symphony and opera for popular song, and Tombre renounces tragedy for pantomime, mediums that lead them individually to embrace anonymity as the highest form of achievement.